2017
DOI: 10.1111/joor.12486
|View full text |Cite
|
Sign up to set email alerts
|

Oro‐facial impairment in stroke patients

Abstract: Stroke is considered one of the leading causes of death and acquired disability with a peak prevalence over the age of 80 years. Stroke may cause debilitating neurological deficiencies that frequently result in sensory deficits, motor impairment, muscular atrophy, cognitive deficits and psychosocial impairment. Oro-facial impairment may occur due to the frequent involvement of the cranial nerves' cortical representation areas, central nervous system pathways or motoneuron pools. The aim of this narrative, non-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
66
3
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 71 publications
(74 citation statements)
references
References 131 publications
3
66
3
2
Order By: Relevance
“…The extensive ongoing feedback and feedforward information provided by the oro‐facial somatosensory inputs to oSI, oMI and CMA is crucial for the preparation, execution, modulation and coordination of the many muscle activities involved in oro‐facial sensorimotor functions such as the positioning of the tongue to help place a food bolus between the teeth and the control of jaw muscles to regulate bite force during chewing (for review, see refs). The critical roles that these three cortical areas play in these functions are particularly evident, and clinically relevant, by way of the functional deficits that can occur in humans when a cortical injury (eg, stroke) affects these areas . Studies in laboratory animals have also shown that damage or experimentally induced inactivation of oM1, oS1 or CMA can disrupt chewing and swallowing and more simple voluntary oro‐facial movements, including the coordination of jaw, tongue and facial movements which is necessary for proper ingestion and transport of food and liquid from the mouth to the oesophagus (eg, refs).…”
Section: Regulation Of Oro‐facial Sensorimotor Functionsmentioning
confidence: 99%
See 4 more Smart Citations
“…The extensive ongoing feedback and feedforward information provided by the oro‐facial somatosensory inputs to oSI, oMI and CMA is crucial for the preparation, execution, modulation and coordination of the many muscle activities involved in oro‐facial sensorimotor functions such as the positioning of the tongue to help place a food bolus between the teeth and the control of jaw muscles to regulate bite force during chewing (for review, see refs). The critical roles that these three cortical areas play in these functions are particularly evident, and clinically relevant, by way of the functional deficits that can occur in humans when a cortical injury (eg, stroke) affects these areas . Studies in laboratory animals have also shown that damage or experimentally induced inactivation of oM1, oS1 or CMA can disrupt chewing and swallowing and more simple voluntary oro‐facial movements, including the coordination of jaw, tongue and facial movements which is necessary for proper ingestion and transport of food and liquid from the mouth to the oesophagus (eg, refs).…”
Section: Regulation Of Oro‐facial Sensorimotor Functionsmentioning
confidence: 99%
“…Nutritional intake and associated ingestive functions may also be compromised in many elderly individuals by the loss of teeth which is particularly common in the elderly . These considerations may especially apply to institutionalised elderly individuals where chewing impairment may be associated with greater risk of mortality, and also apply to elderly persons with neurological problems (eg, stroke) or severe cognitive decline who may have more dental occlusal and related problems affecting their chewing ability …”
Section: Ageing and Oro‐facial Sensorimotor Functionsmentioning
confidence: 99%
See 3 more Smart Citations